THE RELATIONSHIP BETWEEN STUDENTS’ PERCEPTION AND SATISFACTION ABOUT THE IMPLEMENTATION OF ONLINE LEARNING TOWARDS SCIENCE LEARNING OUTCOMES - Khalimatus Syakdiyah; Ria Wulandari (Jurnal Pembelajaran Sains, 2020)
The purpose of this study was to determine the relationship between perceptions and student satisfaction regarding the implementation of online learning on student cognitive learning outcomes in science subjects at SMPN 1 Jabon. The method used in this study was the ex-post facto type of quantitative corelation method. The population used in this study were all students of SMP 1 Jabon class VII with a sample of 68 students. Data collection techniques used were questionnaires and documentation. The data analysis technique used to test the hypothesis was multiple correlation analysis techniques. The results of this study indicate that: 1. There is a relationship between perceptions about the implementation of online learning on the cognitive learning outcomes of students in science subjects, 2. There is a relationship between student satisfaction about the implementation of online learning and student cognitive learning outcomes in science subjects, 3. There is a positive relationship and significant between student perceptions and satisfaction with the cognitive learning outcomes of class VII students in science subjects for the 2019/2020 school year. Where the Fcount price is 5,261. This value is greater than the Ftable value at the 5% significant level of 3.14. So the price Fcount> Ftable.